Quantitative evaluation of microtwins and antiphase defects in GaP/Si nanolayers for a III–V photonics platform on silicon using a laboratory X‐ray diffraction setup. (1st June 2015) - Ping Wang, Yan; Letoublon, Antoine; Nguyen Thanh, Tra; Bahri, Mounib; Largeau, Ludovic; Patriarche, Gilles; Cornet, Charles; Bertru, Nicolas; Le Corre, Alain; Durand, Olivier
<x xml:space="preserve">Abstract</x> This study is carried out in the context of III–V semiconductor monolithic integration on silicon for optoelectronic device applications. X‐ray diffraction is combined with atomic force microscopy and scanning transmission electron microscopy for structural characterization of GaP nanolayers grown on Si. GaP has been chosen as the interfacial layer, owing to its low lattice mismatch with Si. But, microtwins and antiphase boundaries are still difficult to avoid in this system. Absolute quantification of the microtwin volume fraction is used for optimization of the growth procedure in order to eliminate these defects. Lateral correlation lengths associated with mean antiphase boundary distances are then evaluated. Finally, optimized growth conditions lead to the annihilation of antiphase domains within the first 10 nm.